(untitled) - Chapman, Stephen J. (Autralia, 2009)
This book is not primarily a "how to use MATLAB" text. Instead, the book teaches MATLAB as technical programming language in place of other languages such as Basic, Fortran, or C++. Most engineering curricula now require MATLAB and use it as an essential tool throughout the program. At the same time, most engineering curricula require students to become familiar with at least the basics of computer programming.
Keywords: MATLAB,Numerical analysis; Data processing